Choking under pressure of top performers: Evidence from Biathlon competitions - Florian Lindner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
Psychological pressure affects performance. This is especially true for individuals completing precision tasks in decisive situations, such as assessment tests, job talks, or sports competitions. In this paper, I shed light on detrimental effects of pressure on performance, a phenomenon known as "choking under pressure". I analyze a unique setting in which the effect of pressure on performance is naturally observable: Biathlon World Cup competitions. As the last shot in the final bout of shootings is regularly decisive for the victory, pressure is highest on the leader of the competition not to miss this last shot. Using event data from 11 seasons of Biathlon World Cup, I find strong evidence for "choking under pressure", implying that especially leaders are more likely to fail decisive shots. Furthermore, taking more time for the last shootings bout leads to a decrease in performance. Finally, I show suggestive evidence for a momentum effect - after missing a shot during the last shooting bout, the probability of missing the last shot decreases.
Keywords: L83; M51; M54; Z20; L83; 330; choking under pressure; psychological pressure; Biathlon